Case Study: Trend and Prediction of Water Quality Parameter in Sungai Sg. Petani, Kedah - Hittayatullah, Hadif Fadlin; AHMAD NAZRI, MOHD ARIFF (Recent Trends in Civil Engineering and Built Environment, 2021)
Human activity causes and gives the negative effect on the water quality of the river that can harm the human health and damaging the ecosystem (Johnson, 2009)[1]. Forest exploration also causes the increases in runoff and increase in the amount of suspended solids in the water. Besides that, agriculture also affects the river and contributes to the pollution (Jabbar, 2019)[2]. Water pollution in Sungai Sg. Petani, Kedah has affected the source of water for the people in Sungai Petani, but the ecosystem in the river. In October 2010, the amount of waste in the along the river that has been cleaned is 3,027 ton according to (Jabatan Pengairan dan Saliran Negeri Kedah, 2010). The water pollution has become serious and unsafe. There has been many suggestions and solution to prevent the water quality from getting worse. The simplest solution to build a waste trap, and controlling the building development in Sungai Petani. Those solutions are not effective to help improving the water quality in Sungai Sg. Petani for a long period.